Examining Coherence and Cohesion in Civilization Essays. Case of Master Two Students at the Department of English at Laghouat University - Bounif,Sabrina; Ben Redda, Djamel (University of Ammar Theledji -Laghouat, 2020)
Writing in a foreign language is one of the most challenging and complex tasks for language learners. It is a difficult skill that requires considerable effort and practice on the learners’ part to reach an acceptable level of writing. Due to the complexity of this skill, many students fail to produce an adequate piece of writing. For that, This research is concerned on writing skill, especially about coherence and cohesion as important elements in writing. The aim of this research is to find out the students’ usage of coherence and cohesion in writing process. This research adapts descriptive qualitative study. It was conducted in the department of English at Ammar Telidji of Laghouat. The subject of this research is the master two students in academic year 2019/2020. The total number of participants is 15 student. Written essays of American civilization exam are the instrument used to collect the data in this research. The findings of this research show that there were some difficulties faced by the students in maintaining their coherence and cohesion in writing essays, specifically in determining and stating their ideas, fulfilling the supporting details, and using the proper signals, as well as punctuation.